Dog boy - Hornung, Eva (Viking, 2010)
A four-year-old boy named Romochka is abandoned by his mother and uncle and left to fend for himself on the streets of Moscow, with uncounted millions of homeless children and adults. He follows a stray dog to its home in a deserted church celler. There he joins Mamochka, the mother of the pack, and six other dogs and slowly he forgets his human attributes to survive two fiercely cold winters. Romochka attracts the attention of local police, street urchins, and finally, scientists.